1999
DOI: 10.1139/y99-050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of some phospholipase A2and cytochrome P450 inhibitors on rat arterial smooth muscle K+currents

Abstract: The hyperpolarizing factor that is liberated by vascular endothelial cells in response to various agonists, and known to induce relaxation by opening of smooth muscle K+ channels, has been suggested to be a product of cytochrome P450 dependent arachidonic acid metabolism. In this study, the direct influence of two phospholipase A2 inhibitors and of five structurally and mechanistically different cytochrome P450 inhibitors on K+ currents in freshly isolated vascular smooth muscle cells from the rat aorta was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…17‐ODYA, a CYP suicide substrate inhibitor, was utilized in our study because it was reported that many of the commonly used CYP inhibitors such as proadifen (SKF525a), and clotrimazole directly inhibit vascular smooth muscle K + channels (Zygmunt et al ., 1996; van de voorde & Vanheel, 1997; Waldron et al ., 1999). In contrast, 17‐ODYA has been found to be relatively selective for inhibition of EDH activity attributed to CYPs without directly affecting K + channels (Zygmunt et al ., 1996; Vanheel et al ., 1999; Welsh & Segal, 2000). It is also important to recognize that hyperpolarization of porcine coronary arterioles by EETs was inhibited by iberiotoxin (Pratt et al ., 2001), whereas in our preparation iberiotoxin did not affect relaxation.…”
Section: Discussionsupporting
confidence: 89%
“…17‐ODYA, a CYP suicide substrate inhibitor, was utilized in our study because it was reported that many of the commonly used CYP inhibitors such as proadifen (SKF525a), and clotrimazole directly inhibit vascular smooth muscle K + channels (Zygmunt et al ., 1996; van de voorde & Vanheel, 1997; Waldron et al ., 1999). In contrast, 17‐ODYA has been found to be relatively selective for inhibition of EDH activity attributed to CYPs without directly affecting K + channels (Zygmunt et al ., 1996; Vanheel et al ., 1999; Welsh & Segal, 2000). It is also important to recognize that hyperpolarization of porcine coronary arterioles by EETs was inhibited by iberiotoxin (Pratt et al ., 2001), whereas in our preparation iberiotoxin did not affect relaxation.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, 17-ODYA (10 mol/L), which preferentially blocks CYP 4A isoforms, had no effect on the relaxation of rings from either strain ( Figure 4B). The non-isoform-selective CYP-inhibitor miconazole (3 mol/L), which is also known to block potassium channels, 21,22 attenuated relaxations in vessels from WKY as well as SHR ( Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Miconazole, however, also attenuated the maximal EDHF-mediated relaxation in arteries from WKY rats, an effect that may be due to the nonspecific inhibition of K ϩ channels which has been reported as a side effect of some cytochrome P450 inhibitors. 21,22 Taken together, these observations suggest that a major difference in the EDHF-mediated responses recorded in renal arteries from young SHR and WKY rats can be attributed to the differential involvement of a cytochrome P450 epoxygenase that is sensitive to sulfaphenazole…”
Section: Discussionmentioning
confidence: 96%
“…96 Additionally, in numerous vascular preparations from various species, EETs evoke no or minor relaxations and/or hyperpolarization, indicating that in these arteries non-NO-non-PGI 2 -mediated responses are unlikely to rely on this metabolite of arachidonic acid. 7 The lack of selectivity of the available tools 97,98 has made it difficult to determine whether the activation of the endothelial potassium channels IK Ca and/or SK Ca or the release of EETs underlies non-NO-non-PGI 2 -mediated responses. For instance, clotrimazole, a reference inhibitor of cytochrome P450 epoxygenases, also blocks IK Ca .…”
Section: Other Identified Endothelium-derived Hyperpolarizing Substancesmentioning
confidence: 99%